Formative Evaluation of a Home-Based Physical Activity Intervention for Adolescent Girls-The HERizon Project: A Randomised Controlled Trial - Emma S. Cowley; Paula M. Watson; Lawrence Foweather; Sarahjane Belton; Chiara Mansfield; Gabriella Whitcomb-Khan; Isabella Cacciatore; Andrew Thompson; Dick Thijssen; Anton J. M. Wagenmakers (MDPI AG, 2021)
Background. This is a formative evaluation study of the HERizon Project, a home-based multi-component physical activity (PA) intervention for adolescent girls in the UK and Ireland. Although not intended, this study coincided with the initial COVID-19 lockdown restrictions. Methods. A total of 42 female participants, aged 13 to 16 years old (mean = 14.2, SD = 1.1), were randomly allocated to: (i) the HERizon group (n = 22) or (ii) the wait-list control group (n = 20). Participants in the six-week HERizon group were asked to complete three PA sessions each week and engage in weekly behaviour change support video calls. The primary outcome measure was self-reported habitual PA. Secondary outcomes measures included cardiorespiratory fitness (20 m shuttle run), muscular strength (standing long jump), muscular endurance (push up test), and psychosocial outcomes (Perceived Competence Scale, Body Appreciation Scale, Self-Esteem Questionnaire, Behavioural Regulation in Exercise Questionnaire). Quantitative and qualitative process evaluation data were also collected. Outcome measures were assessed at baseline and after the six-week intervention. Results. There was no significant change in habitual PA between groups (LMM group*time interaction: p = 0.767). The HERizon group had significantly increased cardiorespiratory fitness (p = 0.001), muscular endurance (p = 0.022), intrinsic motivation (p = 0.037), and body appreciation (p < 0.003) in comparison to the wait-list control group. All participants in the intervention group completed the intervention and compliance to the intervention was high (participants completed 18 ± 2 sessions). Conclusions. Although no change in PA was observed, HERizon resulted in improved physical fitness and psychosocial outcomes. These preliminary findings, alongside positive findings for feasibility and acceptability, highlight potential benefits from the home-based intervention, thus further investigation is warranted.